Misoginia, patriarcado e subversão em Contos de amor rasgados, de Marina Colasanti - Almeida, Alessandra Oliveira de (2021)
The present work aims to analyze the relations of representation of women with the aspects of misogyny and patriarchy heritage, making counterpoints to these concepts, through the subversion of the female characters chosen for the study, in nine mini-stories from the work Contos de amor rasgados, from 2010, by author Marina Colasanti. This relationship, in this research, is analyzed from the conceptualization of misogyny, patriarchy and subversion and how these concepts interfere in the female action. For the discussions related to the perspective of misogyny and patriarchy, the mini stories “Never neglecting duty”, “No news from the front” and “Honor passed clean” were chosen. For the perspective of women's subversion to these concepts, the mini stories “The milk of the beloved woman”, “When it was no longer needed”, “Never soiling the family”, “Lost was the goal of the morphosis”, “Song for Hua Mu-lan” and “Behind the thick veil”. It is a bibliographic research that is carried out from an articulation between literary and sociological theories and the literary text. For the analysis of the author and her relevance to contemporary Brazilian literature, the following materials were used: Colasanti (1997, 2003, 2008, 2010, 2013, 2014); Spalding (2007, 2008, 2012), Schollhammer (2009), Almeida (2013), Gonzaga (2007), among others, were invited to discuss the mini story genre and its construction in contemporary Brazilian literature. Beauvoir (1970, v. 1 and v. 2), Butler (2017), Tiburi (2002), Grosz (2000) and Rago (2004) are the basis for discussions about gender. For discussions on aspects of patriarchy, the postulates of Piscitelli (2009), Saffioti (1976, 2004) and Xavier (1998) were used. For the analysis of the misogyny perspective, this research used the studies of Bloch (1995), Fonseca (2017) and Bourdieu (2012), which deals directly with male domination. Dalcastagnè's (2005) studies on the role of women in Brazilian literature bring important collaborations to the research. In short, through analysis, it is clear that the relationship between the concepts of misogyny, patriarchy and domination permeate different real and fictional social spaces, with subversion being the answer that the feminine can give to centuries of inferiority, since the female protagonism in the literature corroborates the fight against the derogatory severity that affects women since time immemorial.